Cooperativas escolares e sua influência na formação de jovens: um estudo de caso na ONG Pequena Casa da Criança - Bresciani, Juliana Bergamaschi (Universidade do Vale do Rio dos Sinos, 2020)
Through this formal research, sought to identify the importance of cooperative education from the observation of a school cooperative since its implementation, assessing the impacts on the community in which it is inserted through the activities proposed to young members. The concept and history of cooperativism are part of this paperwork, as well as its branches, principles and values. The dual cooperative dimension: social and economic will be highlighted. It will also address the history of school cooperatives and the importance in the dissemination of cooperative culture, being the basis for Sicredi União Metropolitana, through its members, to have evidence regarding the impact of its social actions. In this sense, it was used a case study of the referenced cooperative to work with, also interviews, socio-historical analysis and actions directly related to the fomentation of a cooperative culture in the community which can generate major changes in the perspective of the members' lives. It is hoped that, when presenting this monograph, it will serve as a stimulus for educators regarding the teaching of the practice of cooperativism in schools and may even become a mandatory subject, since Brazil has a vast market for the development of new cooperatives organizations.
Keywords: Cooperativismo; Educação cooperativa; Cooperativa escolar; Cooperativism; Cooperative education; School cooperative